Advancements in arch analysis and design during the Age of Enlightenment - Garrison, Emily (Kansas State University, 2016)
Prior to the Age of Enlightenment, arches were designed by empirical rules based off of previous successes or failures. The Age of Enlightenment brought about the emergence of statics and mechanics, which scholars promptly applied to masonry arch analysis and design. Masonry was assumed to be infinitely strong, so the scholars concerned themselves mainly with arch stability. Early Age of Enlightenment scholars defined the path of the compression force in the arch, or the shape of the true arch, as a catenary, while most scholars studying arches used statics with some mechanics to idealize the behavior of arches. These scholars can be broken into two categories, those who neglected friction and those who included it. The scholars of the first half of the 18th century understood the presence of friction, but it was not able to be quantified until the second half of the century. The advancements made during the Age of Enlightenment were the foundation for structural engineering as it is known today. The statics and mechanics used by the 17th and 18th century scholars are the same used by structural engineers today with changes only in the assumptions made in order to idealize an arch. While some assumptions have proved to be incorrect, many correctly interpreted behavior and were able to formulate equations for design and analysis that were successfully used to create arches that were structurally sound and more efficient than arches designed by empirical methods. This insight into design during the 18th and 19th centuries can help modern engineers better analyze and restore arches from this era and protect our architectural and engineering history.
Keywords: Arch; Age of Enlightenment; Masonry; Catenary